(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence of late-onset hypogonadism and analyze associated factors among men aged 40 and older at the Andrology Clinic, 108 Military Central Hospital. Subjects and methods: A cross-sectional descriptive study was conducted on 260 men aged 40 years and above. Male hypogonadism was assessed using the ADAM questionnaire and serum testosterone concentration measurements. Results: The highest proportion of participants belonged to the 51-60 age group (34.6%). The prevalence of symptomatic hypogonadism ADAM (+) was 54.6%, while biochemical testosterone deficiency was confirmed in 32.8% of the subjects. Statistically significant associations (p < 0.05) were identified between hypogonadism and several factors, including obesity (BMI ≥ 25 kg/m²), large waist circumference (≥ 90 cm), and the presence of underlying comorbidities. Conclusions: The prevalence of male hypogonadism among the study subjects is considerably high and strongly associated with metabolic disorders and comorbidities. Early screening and management of metabolic risk factors play a pivotal role in improving health outcomes for aging men.